Молекулярные основы взаимодействия гирудина с тромбином - Гершкович, А.А. (Биополимеры и клетка, 1992)
Рассмотрены биохимические, химические и физические подходы к изучению строения гирудина и механизма ингибирования им тромбина. Результаты этих исследований открывают путь для создания синтетических ингибиторов тромбина нового типа. Розглянуто біохімічні, хімічні та фізичні підходи до вивчення будови гірудина і механізму пригнічення їм тромбіна. Результати цих досліджень відкривають шлях до створення синтетичних інгібіторів тромбіна нового типу. Biochemical, chemical and physical methods for study of hirudin-thrombin bounding mechanisms are reviewed. Perspectives of the clinical usage of recombinant hirudin and its small synthetic fragments are observed. The possibility for designing of novel drugs based on the studied hirudin-thrombin interaction mechanisms is shown on example of syntheic hirudin-like inhibitors «hirulogs».